2019
DOI: 10.1186/s12958-019-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous gonadotropin on the transcriptome of human granulosa cells and follicular fluid hormone profiles

Abstract: Background Superovulation treatment had some adverse effects on maturity and development of oocytes. Can superovulation dose of gonadotropins (Gns) affect the transcriptome of granulosa cells and follicular fluid (FF) hormone levels? Methods One leading pre-ovulatory follicle per subject was used from three natural-cycle and four Gn-stimulated patients. Granulosa cells and FF samples were collected from the same leading follicle of each patient. RNA was extracted from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Even fragmentation of ≤ 20% presented with similar OR when compared with fragmentation > 20%. When compared with NC follicles, putative markers associated with oocyte quality and follicle maturation were significantly different from those in gonadotropin-stimulated follicles [21]. Therefore, it is unclear whether the results of our study apply to embryos derived from COS, although similar findings are observed in the previous COS-IVF studies [22,23].…”
Section: Discussionsupporting
confidence: 60%
“…Even fragmentation of ≤ 20% presented with similar OR when compared with fragmentation > 20%. When compared with NC follicles, putative markers associated with oocyte quality and follicle maturation were significantly different from those in gonadotropin-stimulated follicles [21]. Therefore, it is unclear whether the results of our study apply to embryos derived from COS, although similar findings are observed in the previous COS-IVF studies [22,23].…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, for POR women %35 years, the live birth rates per complete cycle of mild stimulation were higher. The effectiveness of mild stimulation in women %35 years may be due to avoiding disturbances on oocyte quality by high gonadotropin dose (20). Previous studies have reported that the live birth rates for POR is independent of controlled ovarian stimulation protocols (21), and that mild protocol leads to live birth rates in POR patients that are comparable to conventional protocols (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, as an indispensable medicine for ovarian stimulation in the ART practice, exogenous Gn is used to promote follicular growth via its influence on the cross-talking among the oocyte, granulosa cell and FF. Gn dose is the main difference in our two protocols, but the effect of this difference on the oocyte development and the mechanism underlying which it affects the oocyte development remain unclear although Lu et al showed that Gn stimulation may potentially induce meiotic errors of human oocytes through analyzing the transcriptome of the granulosa cell after natural and Gn stimulation cycles [ 29 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%